Social criticism and tricky irony in Sanai's mind and language - Rouholah Hadi; Mitra Golchin; Mohammadreza Torki; Sima Rahmanifar (مطالعات زبانی و بلاغی)
If we consider the reality as irregularity and poetry as a coherent whole, one of the instruments of this irregularity in poetry and its coherence can be considered to be irony. The heterogeneous experiences of the poet from his world lead to the emergence of apparently more controversial issues in his poetry. The poet's humorous awareness of the existing contradictions brings the text into an irony, can make reading the poet more of an intellectual challenge, and gives readers a wider view. Sanai's heterogeneous experiences, which are the result of a conflict between his ideals and perceptions with his status quo, are intermingled in his poetry and became a whole new one. The current study was aimed to examine how Sanai's linguistic choices are used to reflect the status quo in the society and to demonstrate his thoughts, beliefs and concerns by evaluating the extent, manner, and use of irony in his poems. Based on the results presented herein, there are often a network of different ironies beside each other in the poetic language of the Sanai, by which his poems were turned into an integrated structure; consequently the general readers can be enjoyed from its appearance, and a particular reader from the discovery of hidden layers. As a representative of the educated stratum, Sanai had considered himself responsible to the common people and tried to reflect their concerns and problems in their work. However, he has been forced to diminish his sharp tongue expression, hence, he had used irony.